TANGGUNG JAWAB PERUSAHAAN PT KIRANA SURYA GEMILANG SEBAGAI TOUR BIDANG PELAYANAN JASA TRAVEL DAN TOUR PARIWISATA CABANG JAWA TENGAH - Tia Nurlina Hapsari, Herman Susetyo, Suradi (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Tourism is one important factor in the economy of Indonesia. This is because the tourism is a cornerstone of economic progress of a country. Tourism typically attract foreign investors needed by each country is growing. Tourism also has the responsibility to bring up the image of that name known in the international world. The more quality tourism services in a country or in an area that is growing and the area known to the world. This study uses empirical judirical approach, which is a method or procedure use to solve the problem by examining secondary data first and then proceed to conduct research on primary data in the field as the study of the implementation of the agreements and standards used by the company’s travel and tourism tour. The results showed that the arrangements regarding the implementation of the contract in the Civil Code to be part of the setting of the consequences of an agreement, as provided in Section 1338 to Article 1341 Civil Code. PT Kirana Surya Gemilang as tourism companies in the travel and tour services have some standardization of tourism related services, are part of the infrastructure facilities / infrastructure that should be considered to meet the relevant needs eg water consumption standards that could affect an area as well as efforts to increase tourism the quality of services performed by PT Surya Kirana Gemilang all related complaints from customers directly taken seriously by the owner and director of PT Kirana Surya Gemilang and on evaluating the performance of all the company's staff. Based on the findings of the study suggested that the company can facilitate improved quality of operational standards, the development of quality tourism services effectively and efficiently so that consumers can be satisfied with the services provided by PT Surya Kirana Gemilang,